If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 5 = 6x Reorder the terms: 5 + 11x = 6x Solving 5 + 11x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + 11x + -6x = 6x + -6x Combine like terms: 11x + -6x = 5x 5 + 5x = 6x + -6x Combine like terms: 6x + -6x = 0 5 + 5x = 0 Add '-5' to each side of the equation. 5 + -5 + 5x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 5x = 0 + -5 5x = 0 + -5 Combine like terms: 0 + -5 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| 8-8x=59-29x | | 3x+20=10x-37 | | 11x+5+6x= | | 400000=101300*9.82*x | | -4(3x+6)=15 | | 8x=4x-14 | | 5+5*7= | | 5x+35=12x-36 | | -2x-2(x-9)=-30 | | 3x+x+10= | | 49-2x=7x | | 14x-8=x+19+8x+7 | | -x+y=-6 | | (5)/(6)*8+(3)/(4)=(11)/(12) | | 7x-15=7x+5 | | 10-8x=102-36x | | 13x-12=x+17+7x | | m+(15)=31 | | 3x+6=x+2+4x-7 | | 9x+1=10x-10+9x-7 | | 6x+7=5x-9 | | 3x-1=5+x+3 | | 5x+2=x+1+3x+4 | | 3x+3=4x-3+4 | | 8=2x+2+16x-12 | | Qs=4p-12 | | 13x-9=7x+5x+6 | | 13x-9=8x+5x+6 | | 3(5x-2)-6=3(3x+2) | | 6(m+4)+7(m+6)= | | 0.6(10x-8)-0.2(5x-4)=6 | | 17x+13=10x+20 |